Effects of antiseizure monotherapy on visuospatial memory in pediatric age. (May 2021) - Operto, Francesca Felicia; Pastorino, Grazia Maria Giovanna; Di Bonaventura, Carlo; Scuoppo, Chiara; Padovano, Chiara; Vivenzio, Valentina; Donadio, Serena; Coppola, Giangennaro
Abstract: Introduction: Visuospatial abilities are fundamental for good school achievements and good daily functioning. Previous studies showed an impairment of visuospatial skills in pediatric patients with epilepsy; pharmacological treatment, although indispensable for the seizure control, could further affect cognitive functions. The aim of our study was to evaluate the visuospatial skills in children and adolescents with different forms of epilepsy well-controlled by antiseizure monotherapy, both at baseline and after one year follow-up, through a standardized neuropsychological assessment. Methods: We recruited 207 children and adolescents (mean age = 10.35 ± 2.39 years) with epilepsy, well controlled by monotherapy with levetiracetam, valproic acid, ethosuximide, oxcarbazepine or carbamazepine and 45 age/sex-matched controls. All the participants performed the Rey-Osterrieth Complex Figure, a standardized test for visuospatial perception and visuospatial memory assessment, at baseline and after 12 month of drug therapy. Age, sex, executive functions, non-verbal intelligence, age at onset of epilepsy, epilepsy duration, epilepsy type, lobe and side of seizure onset were considered in our analysis. EEG, seizure frequency, and drug dose were also recorded. Results: At baseline, the epilepsy group performed significantly worse than controls in the Immediate Recall test but not the Direct Copy test, without differences between epilepsy subgroups. Immediate Recall scores were related to age of seizure onset and epilepsy duration and executive functions. The re-assessment after 1 year showed that the Immediate Recall mean scores were not significantly changed in the levetiracetam and oxcarbazepine group, while they significantly worsened in the valproic acid, ethosuximide and carbamazepine groups. The Immediate Recall scores were correlated to age, age at onset of epilepsy, epilepsy duration, and executive functions. Conclusions: Children with epilepsy may exhibit visuospatial memory impairment compared to their peer, that may be correlated to some features of the epilepsy itself and to the impairment of executive functions. Different antiseizure medications can affect visuospatial memory differently, so it is important monitoring this aspect in pediatric patients. Highlights: Our longitudinal retrospective study was based on 207 pediatric patients, newly diagnosed with epilepsy. We assessed visuospatial perception and memory and before drug therapy and after 12 months of monotherapy with LEV, VPA, ETS, OXC, or CBZ. At reassessment, subjects taking VPA, ETS, and CBZ performed significantly worse while subjects taking LEV and OXC showed no significant changes. Visuospatial memory was significantly related to executive functions. It is important to pay attention to the different tolerability profile of antiseizure drugs on the cognitive profile in pediatric age.